2016
DOI: 10.47678/cjhe.v46i2.185184
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Care and Advocacy for Sexual Assault Survivors on Canadian Campuses

Abstract: Recent media coverage of the rape chant at Saint Mary’s University, the misogynist Facebook posts at Dalhousie’s dental school, and the suspension of the University of Ottawa’s hockey team have brought the topic of campus sexual assault under intense public scrutiny and the media accounts point to a widespread systemic rape culture on Canadian campuses. The objective of this paper is to examine the existing structure of campus sexual assault services at Canadian universities and colleges in order to highlight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…Students may be more likely to perceive a college campus as being safe when they receive timely notifications of crimes committed on and around the university; being aware of crime incidents allows for students to understand the context in which the crimes were perpetrated in order to take preventative measures (Merianos et al, 2017). Unlike the United States, Canada does not have a national requirement for its universities to report campus crime or to implement preventative measures, although since these NCHA data were released in 2013, more policies and procedures have been adopted to address sexual victimization at Canadian universities (Quinlan et al, 2016) U.S. universities eligible to receive federal aid are mandated, under the Clery Act, to report crimes annually and provide students with timely alerts of potential threats or hazardous conditions (Lee, 2017). The Clery Act, supplemented by the SaVE Act also requires universities to report campus sexual assaults, intimate partner violence, and stalking (Cox, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Students may be more likely to perceive a college campus as being safe when they receive timely notifications of crimes committed on and around the university; being aware of crime incidents allows for students to understand the context in which the crimes were perpetrated in order to take preventative measures (Merianos et al, 2017). Unlike the United States, Canada does not have a national requirement for its universities to report campus crime or to implement preventative measures, although since these NCHA data were released in 2013, more policies and procedures have been adopted to address sexual victimization at Canadian universities (Quinlan et al, 2016) U.S. universities eligible to receive federal aid are mandated, under the Clery Act, to report crimes annually and provide students with timely alerts of potential threats or hazardous conditions (Lee, 2017). The Clery Act, supplemented by the SaVE Act also requires universities to report campus sexual assaults, intimate partner violence, and stalking (Cox, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Together, this legislation compels all American institutions of higher learning to report crime statistics for the last three years, notify campuses constituents of campus crime, and provide prevention programming among other things. Canadian universities do not have legal requirements equivalent to the Clery Act, and only recently have Canadian universities devoted some resources to developing and implementing sexual assault prevention strategies (Quinlan, Clarke, & Miller, 2016;Weikle, 2016). A lack of focus on crime prevention on Canadian college campuses could be tied to students reporting higher levels of victimization but could also suggest that they have higher levels of fear since their perceptions may not be rooted in fact.…”
Section: Us and Canadian College Students And Fear Of Crimementioning
confidence: 99%
See 1 more Smart Citation
“…Presently, with 1/3 of first year students subjected to sexual assault, sexual violence on university and college campuses is an ongoing and important issue for post-secondary institutions (Senn et al, 2014). In North America, 23.1% of female-identified undergraduate students and 21% of transgender or gender nonconforming students have experienced an incident of sexual violence on campus, which indicates that first-year students, transgender or gender nonconforming students, and students who identify as women 3 appear to be at a higher risk of being subjected to sexual violence (Chiara & Lavina, 2014;Garcia et al, 2011;RAINN, 2016;Senn et al, 2014;Quinlan, Clarke, & Miller, 2016;Tamburri & Samson, 2014).…”
Section: Post-secondary Campusesmentioning
confidence: 99%
“…Canadian universities also appear ill-equipped to deal with sexual violence (Quinlan et al, 2016). For example, at the Université du Québec à Montréal a study found that 3,400 (or 36.9% of their participants) had been sexually assaulted by someone linked to their university, with 42% of those being victimized more than once (Enos, 2017).…”
Section: Introductionmentioning
confidence: 99%